Perceptions of Female Adolescents on Job as Skilled Labour in the Construction Industry of Malaysia - Masidah*, Abdul Majid; Wardah Fatimah, Mohammad Yusoff; Abdul Razak, Sapian (INTI International University, 2019)
Shortage of local skilled workers still exists in the construction industry of Malaysia and this in general may affect its sustainability in the long term if the problem is allowed to continue. Presently, the main contractors have to employ foreign workers from less developed countries in order to fulfil the needs of manual manpower since construction in Malaysia is largely a labour intensive industry. However, the employment of foreign workers is not the solution which the country should adopt as their presence brings a lot of socio-economic problems to the country apart of having poor skills in performing construction work. It is suggested that the construction industry of Malaysia should not only attracting local male youth but also start to encourage female to become construction skilled workers to widen up the pool of talents. The present paper reports the findings from a survey conducted among female adolescents in Selangor in order to have some understanding on how female perceived the job as construction skilled workers in the construction industry of Malaysia.